Mapping QTLs for Pyricularia leaf spot, nematode resistance, and yield related traits in pearl millet [Cenchrus americanus (L.) Morrone] - Vutla, Sairam; Knoll, Joseph E.; Sankuratri, Anvesh; Nayak, Risha G.; Liu, Limei; Chee, Peng W.; Karthikeyan, Raghupathy; Fakrudin, Bashasab; Thudi, Mahendar; Timper, Patricia; Harris-Shultz, Karen; Wallace, Jason G.; et al. (Frontiers in Plant Science, 2025)
Pearl millet [Cenchrus americanus (L.) Morrone, formerly Pennisetum glaucum (L.) R. Br.] is the sixth most important cereal globally and is used for forage and feed in the U.S. To identify genomic regions governing important physiological, agronomic and yield related traits, a recombinant inbred line population derived from the cross between Tift 99D2B1 × Tift 454 was phenotyped in the field in 2006, 2007 and 2013. In addition, the population was phenotyped for root-knot nematode resistance in the greenhouse during 2009. Using a previously generated genetic map containing 505 single nucleotide polymorphism markers and composite interval mapping, we identified 45 QTLs for eight traits (plant height, stem diameter, days to heading, panicle diameter, panicle length, 1000 seed weight, Pyricularia leaf spot disease, and root-knot nematode egg mass) across almost all linkage groups. These QTLs explained 6.31 to 32.51% of phenotypic variance for each trait and were consistently detected over different environments. Plant height and days to heading were colocalized on LG2 and LG5 showing maturity and plant height are linked and influence each other, similarly to other cereal crops. Interestingly, 5 of 19 QTLs linked to plant height, stem diameter, panicle diameter, and panicle length colocalized to the same locations on LG3, indicating breeding for one trait could simultaneously improve the other. The markers and genes identified in the present study can be used in developing high yielding pearl millet varieties using marker-assisted selection.